Does the Excellent Enactment of Highest Strengths Reveal Virtues? - Giuliani, Fiorina; Ruch, Willibald; Gander, Fabian (Frontiers in Psychology, 2020)
Two studies examined the assumption that character strengths enable virtues and facilitate the fulfillments that constitute the good life. Study 1 validated a “layperson’s excellent enactment of highest strengths paradigm”. This paradigm states that more appropriate assignments of character strengths to virtues are obtained when based on descriptions of highest character strengths enacted in an excellent way, than when based on lowest character strengths, or typical enactments. A sample of N = 230 German speaking participants provided descriptions of situations in which they enacted their highest and lowest strengths excellently and typically, and rated these situations on the degree of the six core virtues, strength expression, fulfillment, and intellectual and moral quality. Behavior examples of highest strengths excellently enacted were rated higher and with higher differentiation in the dependent variables than typical enactments or lowest strengths, thus confirming the paradigm. In Study 2, we applied the paradigm: A second sample of N= 113 German speaking participants rated a selected subset of strengths-behaviors of layperson’s excellent enactment of highest strengths collected in Study 1 in regard of their degree of the six core virtues. Results confirmed previous convergent and discrepant findings with the theoretical VIA classification. We can conclude, that the excellent enactment of highest strengths does indeed reveal virtues. Future studies should use the paradigm and examine culturally diverse samples with different methods for further examining the VIA classification.